GREEN SUPPLIER SELECTION PRACTICES AND ITS IMPLICATIONS OF GREEN PURCHASING: CASE STUDY AT 5 STARS HOTEL IN BALI - I Ketut Astawa; I Ketut Budarma; Cokorda Istri Sri Widhari (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2020)
Purpose: The purpose of this study is to examine the practice of selecting green suppliers conducted by companies to be environmentally friendly and how these practices have implications for purchasing green products in 5-star hotels in Bali. Research methods: This study is guided by the green supply chain management model and the green selection model. A descriptive research design is used. Data were collected using a questionnaire. The population consists of 63 employees from companies that supply room supplies, food & beverage, chemical, and Spa. Data were analyzed using SPSS and presented using tables, graphs, frequencies, and percentages. Results and discussions: The study revealed that the selection of environmentally friendly suppliers had a positive and significant effect on the implementation of environmentally friendly purchases. The implications of selecting green suppliers create new market opportunities. Hotel cooperation with suppliers is getting closer and mutually committed to operational purchasing activities. Conclusion: The study revealed that the selection of environmentally friendly suppliers had a positive and significant effect on the implementation of environmentally friendly purchases. The indication was that green supplier selection is a major factor that influences the implementation of green purchasing at 5 stars hotel in Bali.